From defence mechanism to insufficient bladder control: Dutch experts on enuresis nocturna in an age of developing child sciences (c. 1950-1990). Issue 3 (4th May 2021) - Smit, Milou; Bakker, Nelleke
ABSTRACT: This article discusses the conceptualisation of enuresis nocturna by Dutch experts between c .1950 and 1990, years in which across the West new child sciences rapidly developed. Today, bedwetting is conceived as a mental illness caused by a mixture of nature- and nurture-bound factors. Have organic and environmental causes always figured as twins, even in the post-war decades of predominant environmentalism in psychological theory and clinical practice? Or is only the more recent biological turn in psychiatry responsible for a revaluation of organicism in expert discourses on the aetiology and treatment of childhood mental illnesses such as enuresis nocturna ? Using Ian Hacking's dynamic nominalism as interpretive framework, the article shows that, in the Dutch case, environmental factors continued to be referred to after the biologising of children's mental problems, alongside an increasingly important role for brain-related, physiological and genetic causes of enuresis nocturna .